2009
DOI: 10.1042/bsr20080111
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of specific binding of free cholesterol by the steroidogenic acute regulatory protein: evidence for a role of the C-terminal α-helix in the gating of the binding site

Abstract: Steroidogenesis depends on the delivery of free cholesterol to the inner mitochondrial membrane by StAR (steroidogenic acute regulatory protein). Mutations in the StAR gene leads to proteins with limited cholesterol-binding capacity. This gives rise to the accumulation of cytoplasmic cholesterol, a deficit in steroid hormone production and to the medical condition of lipoid congenital adrenal hyperplasia. A detailed understanding of the mechanism of the specific binding of free cholesterol by StAR would be a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 52 publications
(76 reference statements)
5
45
1
Order By: Relevance
“…This hydrophobic cluster around this residue has been proposed to stabilize the C-terminal helix in a closed conformation [30]. It has been suggested that the α4 helix would undergo unfolding during ligand binding [30,31]. The conservation of Trp147 across the domain family indicates that a lipid-binding mechanism via local unfolding or a significant conformational change in the C-terminal helix could be a family-wide phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hydrophobic cluster around this residue has been proposed to stabilize the C-terminal helix in a closed conformation [30]. It has been suggested that the α4 helix would undergo unfolding during ligand binding [30,31]. The conservation of Trp147 across the domain family indicates that a lipid-binding mechanism via local unfolding or a significant conformational change in the C-terminal helix could be a family-wide phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…4). This hydrophobic cluster around this residue has been proposed to stabilize the C-terminal helix in a closed conformation [30]. It has been suggested that the α4 helix would undergo unfolding during ligand binding [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These side chains create hydrophobic anchoring points favorable for a stabilizing clamp between ␣-helix 4 and the core of the protein. It is expected that upon binding of cholesterol to StAR, this clamping mechanism would help stabilize the complex by shielding it from the solvent exposure, until its later release during the steroidogenesis [22]. To gain insight into the molecular behavior of StAR at the atomic level, we conducted MD simulations on the WT protein, the ␣-helix 4 mutants (F267Q, L271N, and L275P) and the salt bridge (E169M/R188M) mutant and emphasized on the variation of their radius of gyration (Rg).…”
Section: Simulations Of Wt Starmentioning
confidence: 99%
“…We hypothesize that these clinical mutations alter the binding affinity of StAR for cholesterol and that this promotes its accumulation in LCAH [22]. Alteration of the ligand binding affinity of a protein requires an understanding of the effect of mutating individual residues in the ligand-binding site and the overall structure of the protein [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation